Efektifitas kelas antenatal sebagai pencegahan retensi berat badan postpartum - Dini Puspita Sari; Muhammad Primiaji Rialihanto; Almira Sitasari; Tri Siswati (Poltekkes Kemenkes Aceh, 2025)
Background: The curriculum of the nutritional education program can influence the success of nutrition education interventions through antenatal classes. Delivering education via antenatal classes is one method to address postpartum weight retention.Objectives: To determine the effectiveness of the enriched antenatal class intervention in increasing mothers' knowledge and attitudes in postpartum weight retention.Methods: This study adopts a pre-experimental research design with a one-group pretest-posttest approach. The study sample comprises 24 pregnant women in their first and second trimesters attending Community Health Center Gamping II. The intervention spanned two days, with the first day consisting of lectures and a question-and-answer session, and the second day involving practical food selection exercises. The data utilized in this study includes primary data obtained directly from the participants and secondary data obtained indirectly from respondents. Univariate analysis was employed to analyze minimum, maximum, mean, and standard deviation values. For bivariate analysis of the knowledge questionnaire, the Wilcoxon test was used, while the attitude questionnaire was analyzed using the Paired Samples t-test.Results: The mean knowledge score before the intervention was 4,46, which increased to 9,17 after the intervention (p=0,001). Similarly, the mean attitude score before the intervention was 105,75, which increased to 140,21 post-intervention (p=0,001). There was a significant difference in knowledge and attitude scores after implementing the antenatal class (p-value= 0,001).Conclusion: An antenatal class curriculum can be used to prevent postpartum weight retention.